Infrared thermography (IRT) applications for building diagnostics: A review - Kylili, Angeliki; Fokaides, Paris A.; Christou, Petros M.; Kalogirou, Soteris A. (My University, 2014)
Infrared thermography (IRT) has met an extensive popularity among the non-destructive technologies for building diagnostics, especially with the increasing concerns of energy minimisation and low energy consumption of the building sector. Its popularity for a broad range of applications can be attributed to its non-contact safe nature, its usefulness and effectiveness, as well as the energy and cost savings it can achieve. This paper reviews the state-of-the-art literature and research regarding the passive and active infrared thermography. The fundamentals of IRT are thoroughly explained and the thermographic process for building diagnostics is presented. This work also presents the fields of applicability of IRT with a focus on the building sector, as well as the advantages, limitations and potential sources of errors of IRT employment. Additionally previous non-destructive testing (NDT) studies that employed passive, active pulsed, and active lock-in thermographies for building diagnostics are presented. A review of the thermal image analysis methods and the future trends of thermal imaging are also included in this work. It can be concluded that while IRT is a useful tool for the characterisation of defects in the building sector, there is great prospect for the development of more advanced, effective and accurate approaches that will employ a combination of thermography approaches.
Keywords: Active thermography; Infrared thermography; Locked in thermography; Non-destructive testing; Passive thermography; Pulsed thermography